2011
DOI: 10.3892/ijo.2011.905
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative potential of curcumin in androgen-dependent prostate cancer cells occurs through modulation of the Wingless signaling pathway

Abstract: Abstract. Activation of the Wingless (Wnt)/ß-catenin signaling pathway contributes to prostate tumorigenesis and metastasis. Depending of the stage of prostate cancer development, current drug therapies are of limited efficiency, so that prevention with natural compounds appears as an attractive strategy especially due to the slow progressive development of prostate cancer. We report here that the chemopreventive agent curcumin from the rhizome of Curcuma longa was able to affect cell proliferation of androgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…β-Catenin is an essential transcriptional co-regulator in the canonical Wnt signaling pathway, forming complexes with the TCF/LEF (T cell-specific transcription factor/lymphoid enhancer-binding factor 1) family of transcription factors to control target gene expression. Recent study revealed that Wnt/β-catenin signal path also acts as a negative regulator of both basal and stress-induced autophagy [37], [38], [39]. Our study found that resveratrol suppresses Wnt/β-catenin signaling pathway in breast CSCs in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 57%
“…β-Catenin is an essential transcriptional co-regulator in the canonical Wnt signaling pathway, forming complexes with the TCF/LEF (T cell-specific transcription factor/lymphoid enhancer-binding factor 1) family of transcription factors to control target gene expression. Recent study revealed that Wnt/β-catenin signal path also acts as a negative regulator of both basal and stress-induced autophagy [37], [38], [39]. Our study found that resveratrol suppresses Wnt/β-catenin signaling pathway in breast CSCs in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 57%
“…In addition to its role as a potentially potent chemosensitizer, curcumin is also a promising radiosensitizer in a wide variety of cancer cells (5255). Curcumin has also been shown to suppress the growth of numerous cancer cells, including those from cancer cells of the prostate (56), biliary (57), pituitary gland (58), oral (59), and uterine leiomyoma (60). …”
Section: Biological Activities Of Curcuminmentioning
confidence: 99%
“…Previous studies have demonstrated that CUR exerts inhibitory effects on various types of cancer, including bladder cancer, prostate cancer, colon cancer, liver cancer and breast cancer (1922). DMC, which is a structural analogue of CUR, also exhibits antitumor effects (14) and strongly inhibits proliferation of prostate cancer cells (23).…”
Section: Discussionmentioning
confidence: 99%